PENGARUH BUDAYA KERJA, LINGKUNGAN KERJA, KOMPENSASI FINANSIAL, DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN TETAP PT. SURABAYA PANEL LESTARI GRESIK - Siti Aizah (Jurnal Manajerial, 2019)
This research aims to test the influence of the culture of the Organization, the work environment, Financial Compensation, and Non financial Compensationperformance against permanent employees of PT. Surabaya Panel Lestari Gresik. Then conducted a review of the literature and the preparation of the hypothesis, as well as the data obtained from the dissemination of questionnaires against 62 permanent employees of PT. Surabaya Panel Lestari Gresik using Total Sampling. Testing is done using multiple Linear regression analysis. The results of the analysis show that organizational culture does not have an effect on the variable performance of the employees, the influential working environment significantly to the performance of the employee, financial compensation is a significant effect on performance of employees and Non financial compensation effect significantly to the performance of the employee. The culture of the Organization, the work environment, Financial Compensation, Non financial Compensationsignificant effect simultaneously against variable employee performance.